Arahan Mitigasi dan Evakuasi Bencana Alam Tanah Longsor di Kecamatan Maiwa Kabupaten Enrekang - Rayhan R. Syams, Muhammad; Syafri, Syafri; Rasyidi, Emil Salim (Journal of Urban Planning Studies, 2024)
Abstract. The purpose of this study is to determine the level of disaster risk and be able to formulate directions for mitigation and evacuation of landslide natural disasters at the research site. The method used in this study is descriptive qualitative. The analytical method to determine the level of vulnerability, vulnerability, capacity, risk to mitigation is superimpose analysis. The results of research that have been conducted regarding the level of disaster risk are 3 (three), namely high, medium, and low. Then there are 2 (two) structural and non-structural mitigation directions at the research site. The evacuation route is along the connecting local road between Tuncung and Tapong villages and the local road in Tanete village. The mitigation directives and evacuation routes are focused on areas that have a high risk of landslides.